Introduction to English in Early Childhood Using the Bilingual Interactive Read-Aloud Method at TwinQ Kids School - Fadillah Sandy; Lintang Muliawanti (Urecol Journal. Part F: Community Development, 2021)
Introduction to English from an early age is needed to prepare the next generation for success in the globalization era. Unfortunately, not all early childhood education institutions have English teachers. Therefore, this activity aims to introduce English to early childhood at TwinQ Kids School. The Interactive Read-Aloud (IRA) method was chosen, which was delivered bilingually (English-Indonesian). This program has an impact on the development and strengthening of English linguistics in students and shows positive involvement in behavioral, cognitive, and affective aspects during the activity.